Influence of Sugarcane Bagasse Biochar Amendment on Low Plastic Clay Soil Performance: A Novel Approach for Geotechnical and Geo-environmental Applications - Yadav, Shailesh Kumar; Raj, Amrit; Bag, Ramakrishna (Indonesian Geotechnical Journal, 2024)
The application of biochar in geotechnical and geoenvironmental engineering remains relatively understudied, particularly concerning its impact on soil properties when mixed with sugarcane bagasse. This study investigates the influence of sugarcane bagasse-derived biochar on the strength and water retention behavior of low plastic clay soil, representing a novel contribution to the field. Biochar, a carbon-rich material produced by the pyrolysis of organic biomass, has garnered attention for its potential to enhance soil properties and mitigate environmental challenges. Five different percentages of bagasse biochar (0%, 1%, 2%, 3.5%, and 5%) were incorporated into the low plastic clay soil to prepare biochar-amended soil specimens. Unconfined compressive strength and water retention tests were conducted to evaluate the mechanical and hydraulic properties of the amended soils. The findings reveal that the water retention capacity of the biochar-amended soil increased with the addition of bagasse biochar. This observation suggests that biochar incorporation enhances the soil's ability to retain moisture, potentially beneficial for mitigating soil moisture fluctuations and supporting plant growth in geoenvironmental applications. Furthermore, the study also highlights a positive impact on the strength properties of the soil with a 22.1% increase for 1% biochar content compared to no-amended after 28 days. This increase in strength was attributed to changes in soil structure, pore distribution, and inter-particle bonding induced by the presence of biochar. In conclusion, Biochar amendment offers potential for enhancing soil water retention and strength properties and the use of sugarcane bagasse-derived biochar in low plastic clay soil presents promising opportunities for geoenvironmental engineering applications.